Improving the performance of transportation networks: A semi-centralized pricing approach - CAO, Zhiguang (Institutional Knowledge at Singapore Management University, 2021)
Improving the performance of transportation network is a crucial task in traffic management. In this paper, we start with a cooperative routing problem, which aims to minimize the chance of road network breakdown. To address this problem, we propose a subgradient method, which can be naturally implemented as a semi-centralized pricing approach. Particularly, each road link adopts the pricing scheme to calculate and adjust the local toll regularly, while the vehicles update their routes to minimize the toll costs by exploiting the global toll information. To prevent the potential oscillation brought by the subgradient method, we introduce a heavy-ball method to further improve the performance of the pricing approach. We then test both the basic and improved pricing approaches in a real road network, and simultaneously compare them with several baselines. The experimental results demonstrate that, our approaches significantly outperform others, by comprehensively evaluating them in terms of various metrics including average travel time and travel distance, winners and losers, potential congestion occurrence, last arrival time, toll costs and average traffic flows, with two different O-D profiles.